An Approach to Integrate IoT and Mobile Technology for Remote Camera Management - Noureddin Mohammed Elazumi; Abubaker Kashada; Mohamed Alforgani (Surman Journal of Science and Technology, 2021)
The goal of most control systems is to create external tools that can manage larger, more complex machines. Recently, however, control devices have become more compact, with smaller smart devices being utilized to control larger machines. This shift offers significant advantages in industries, particularly in terms of mobility and simplicity. This study proposes a camera control system designed to use mobile devices through wireless technology, offering enhanced mobility at a lower cost. The system enables a mobile phone to control an intelligent IP camera via Bluetooth and was developed using the Java Application Development Kit (JDK). The design and implementation of this system were informed by research into existing technologies and tools, as well as methods used to bring the research to fruition. several potential areas for future research and development were identified to further improve the system’s capabilities.